Similitude and Rebound Effect of Drugs - Teixeira, Marcus Zulian (Homœopathic Links, 2014)
Samuel Hahnemann systematised the homeopathic model and the effects of drugs on the state of human health, describing a primary action of the drugs followed by a secondary and opposite action of the organism. In modern pharmacology, this secondary action is known as the rebound effect or paradoxical reaction of the organism, being described after the discontinuation of several classes of palliative (enantiopathic) drugs, i.e., those that act according to the principle of contrary (contraria contrariis curentur). Besides being able to cause severe and fatal iatrogenic events when appearing after the palliative use of modern drugs, the rebound effect might awaken a healing reaction if the very same drugs involved were employed according to the principle of similitude (similia similibus curentur).
Keywords: Homeopathy; Pharmacology; Adverse effect; Secondary effect; Rebound effect; Paradoxical reaction; Law of similarity